Pengaruh Anxiety terhadap Performa Atlet Karate Tahun 2022 - Putri, Tika Ameliyana; Kusuma, Donny Wira Yudha (Indonesian Journal for Physical Education and Sport, 2023)
This study aims to determine how the implementation of character values in state elementary schools in Sirampog District, Brebes Regency. The method used in this research is descriptive qualitative. Data analysis used interactive model analysis, namely data collection, data reduction, data presentation and conclusion drawing. The results showed that the implementation of the character load was carried out based on the lesson plan. The contents of the characters seen in physical education learning are religious, disciplined, independent, enthusiastic, courageous, cooperative, hard working, sporty, nationalist and responsible. The differences in character emphasis presented are: at SDN Sridadi the emphasis is on the character of hard work, cooperation and sportsmanship, while at SDN Igirklanceng the emphasis is more on the nationalist character. The strategy used is understanding character values ​​and habits in school. There are inhibiting factors in character implementation, namely environmental factors. The conclusion from this study is that the implementation of character values of state elementary schools in Sirampog District, Brebes Regency has been carried out by Physical Education teachers. However, there are obstacles that become obstacles in implementation, namely environmental influences and the teacher's lack of maximum performance in evaluating student character education.